Pengaruh Rasio Kesehatan Bank (CAR, NPF, FDR, BOPO) Terhadap Return On Assets pada Bank Umum Syariah di Indonesia - Heidy Paramitha Devi (Politeknik Ganesha Medan, 2021)
Banking financial performance is reflected in their financial reports. Assessment of bank performance can be measured through financial ratio analysis approaches, one of which is the ratio of the bank's ability to generate profits or ROA. In generating good profits, a bank must be said to be healthy, the bank's health ratio which can describe the bank's health condition includes the level of capital adequacy, liquidity ratios, and bank operating expense ratios. The aims of the research are to find out and analyze the influence of the level of bank health ratio on the financial performance of Syariah Public Banks. The population are Bank Umum Syariah (BUS) in Indonesia which is registered in Bank Indonesia directory period 2016- 2020 that is 14 Bank Syariah. This study combined of a research object and one-time dimension, measurement by data analysis tools eviews 8, the test model chosen is the Fixed Effect Model - Least Square Dummy Variable. F test results showed that six variables simultaneously affect the amount of lending with the value of Prob (F-statistic) 0.000000. Hypothesis test results showed that CAR and NPF ratios have no influence to ROA, while FDR has a positive significant influence to ROA and BOPO ratio has a negative influence on ROA.